(untitled) (World Bulletin of Management and Law, 2023)
The article discusses the philosophical and religious teachings of Abu Ali ibn Sina, one of the Eastern thinkers, in his works "Treatise on the Distribution of Beings", "Donishnama", "Classification of Intellectual Sciences". The human mind is enriched and developed by studying various subjects. Ibn Sina also pays great attention to the science of logic. Reason is interpreted as the criterion of any knowledge and practical activity. The relevance of Ibn Sina’s thoughts such as "Any knowledge that is not measured on the scales of reason cannot be true, therefore, it is not real knowledge." The author emphasizes that in Ibn Sina’s work, attention to the examination of the structure of science, the determination of the order of sciences, and their classification occupy a special place. These philosophical, religious and scientific views of Ibn Sina have not lost their importance even today, when spiritual poverty is recognized as a tragedy of the times.